A method for preparing a carbon black-based composite conductive agent for automotive lithium batteries
By depositing and modifying carbon black-based composite conductive agent on MOF-Ni3 (HITP)2, the problems of poor charging and dispersion of existing conductive agents at high rates are solved, and the conductive properties are significantly improved and the stability is enhanced.
Patent Information
- Application Number
- CN202411570032.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The conductive agents used in existing lithium iron phosphate batteries, such as acetylene black and conductive carbon black, have poor charging and discharging effects at high rates, high dispersion costs of carbon nanotubes and graphene, and the dispersion of conductive agents with smaller particle size is difficult to disperse, which affects the stability of conductive properties.
The conductive carbon black was deposited in the surface and voids of MOF-Ni3 (HITP)2 by vapor deposition method, and surface modification was carried out in combination with a special spray to prepare a carbon black-based composite conductive agent to improve the dispersion and conductivity stability of the conductive agent.
It significantly improves the conductivity and high-rate charging and discharging efficiency, enhances the dispersion of the conductive agent and the conductivity stability of long-term use, and reduces the dispersion difficulty and cost in the production process.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy automobile lithium batteries, and specifically relates to a method for preparing a carbon black-based composite conductive agent for automobile lithium batteries. Background Art
[0002] As the power source of electric vehicles, lithium batteries have many advantages: high energy density, long service life, and high charging and discharging efficiency. In recent years, lithium battery technology has continued to advance. On the one hand, the development of materials science has continuously improved the performance of key components such as positive and negative electrode materials, conductive materials, electrolytes, and separators of lithium batteries. For example, new ternary cathode materials and lithium iron phosphate cathode materials have higher specific capacity and better safety; the research and development of solid electrolytes is expected to further improve the safety and energy density of lithium batteries.
[0003] Among them, lithium iron phosphate batteries have been widely used in electric vehicles, energy storage systems and other fields. The positive and negative conductive agents play a vital role in lithium iron phosphate batteries. In the early research on lithium iron phosphate batteries, people gradually realized that the conductivity of lithium iron phosphate itself is low. This characteristic limits the charge and discharge performance and energy output of the battery, so it is necessary to add a conductive agent to improve the conductivity of the electrode. The conductive agents initially used were mainly traditional carbon black materials, such as acetylene black, conductive carbon black, etc. These granular conductive agents are relatively cheap, easy to use, and can improve the conductivity of the electrode to a certain extent. However, their conductive properties still have room for improvement, and their performance in high-rate charge and discharge conditions is not satisfactory, and carbon black with smaller particle size is easy to agglomerate in the slurry and difficult to disperse evenly.
[0004] With the continuous development of materials science, new conductive agents are gradually being developed and applied. Carbon nanotubes are an important representative of them. Carbon nanotubes have a high aspect ratio and excellent conductivity. They can form a good conductive network in the electrode and improve the transmission efficiency of electrons. However, the preparation process of carbon nanotubes is relatively complicated and difficult to be widely used. In addition, the dispersion of carbon nanotubes is poor. There are strong van der Waals forces between carbon nanotubes, which are easy to agglomerate in the positive electrode slurry, resulting in poor dispersion in the electrode material. If the dispersion is uneven, it will affect the formation of the conductive network of the conductive agent in the electrode, thereby reducing the performance of the battery. Graphene is also a new type of conductive agent that has attracted much attention in recent years. Graphene is a two-dimensional sheet structure material composed of carbon atoms, with extremely high specific surface area and excellent conductive properties. At the same time, graphene is expensive and difficult to disperse. Graphene is a sheet structure, and there are strong van der Waals forces and π-π interactions between the sheets, which makes graphene easy to agglomerate in the positive electrode slurry and difficult to disperse evenly; this will not only affect the performance of the graphene conductive agent in the electrode, but also increase the difficulty and cost of dispersion in the production process. In addition, graphene also has functional group problems. Graphene prepared by redox method or biomass catalysis method usually contains a large number of surface functional groups such as carboxyl, hydroxyl, and epoxy. The presence of these functional groups will increase the amount of electrolyte absorbed and reduce the energy density of the battery on the one hand; on the other hand, it will reduce the conductivity of graphene to a certain extent, affecting the performance of the battery.
[0005] In practical applications, the selection and use of positive and negative electrode conductive agents need to comprehensively consider multiple factors, such as battery application scenarios, performance requirements, etc. For application scenarios with high power performance requirements such as electric vehicles, it is necessary to select conductive agents with excellent conductivity. Therefore, it is necessary to continuously develop more efficient and practical conductive agents to support the performance of batteries and promote the continuous development of lithium iron phosphate battery technology. Summary of the invention
[0006] The high-rate charge and discharge effects of acetylene black and conductive carbon black conductive agents used in existing lithium iron phosphate batteries are not good. The dispersion cost of carbon nanotubes and graphene is high, and the dispersion of conductive agents with smaller particle sizes is difficult, which affects the stability of conductive performance. The present invention provides a method for preparing a carbon black-based composite conductive agent for automotive lithium batteries, wherein the conductive carbon black is deposited on the surface and voids of MOF-Ni3(HITP)2 by vapor deposition to obtain MOF-Ni3(HITP)2-loaded carbon black, and then a special spray is used to modify the surface of MOF-Ni3(HITP)2-loaded carbon black to obtain a carbon black-based composite conductive agent, which can greatly improve the dispersibility of the conductive agent, improve the conductivity and long-term conductive stability, and has good high-rate charge and discharge efficiency. The specific technical scheme is as follows:
[0007] A method for preparing a carbon black-based composite conductive agent for automotive lithium batteries comprises the following steps:
[0008] S1, sample pretreatment: drying the MOF-Ni3(HITP)2 powder and then irradiating it with ultraviolet light to increase the surface activity;
[0009] S2, sample loading: the pretreated MOF-Ni3(HITP)2 powder is evenly spread in an open container, placed in a chemical vapor deposition furnace, and evacuated to remove air and impurities;
[0010] S3, introducing gas: introducing gas into the chemical vapor deposition furnace, wherein the gas contains a carrier gas and a carbon source gaseous precursor, and the volume ratio of the carrier gas to the carbon source gaseous precursor is 100:(3-10);
[0011] S4, depositing carbon black: heating the chemical vapor deposition furnace to 600°C to 800°C, with a gas flow rate of 800mL / min to 1500mL / min, and performing a deposition reaction for 1.5h to 3h to deposit the conductive carbon black on the surface and in the pores of MOF-Ni3(HITP)2, cooling and taking out, and obtaining MOF-Ni3(HITP)2 loaded carbon black;
[0012] S5, surface modification:
[0013] S5.1: Mix and prepare the following according to the mass ratio: water: polyvinyl alcohol: water-based polyurethane: behenamidopropyl dimethylamine: fatty alcohol polyoxyethylene ether = (80-100): (1-2.5): (0.5-1.5): (0.5-1.5): (0.3-0.8) to obtain a spray;
[0014] S5.2: The surface of MOF-Ni3(HITP)2 loaded with carbon black is modified by a fluidized spraying method, and then dried to obtain a carbon black-based composite conductive agent for automotive lithium batteries.
[0015] In S1 of the above preparation method, the drying is vacuum drying, the drying temperature is 60° C. to 80° C., and the drying time is more than 20 minutes.
[0016] In S1 of the above preparation method, the ultraviolet irradiation time is 30 min to 50 min.
[0017] In S3 of the above preparation method, the carrier gas is nitrogen or argon, and the carbon source gaseous precursor is acetylene.
[0018] In S3 of the above preparation method, the flow rate of the gas is 500 mL / min to 1500 mL / min.
[0019] In S4 of the above preparation method, the heating rate is 5°C / min to 8°C / min.
[0020] In S5.1 of the above preparation method, the mixing temperature is 40°C to 60°C.
[0021] In S5.2 of the above preparation method, the parameters of the fluidized spray are: spray inlet temperature 30°C to 35°C, spray speed 0.25L / min to 0.35L / min, atomization pressure 0.5MPa to 0.6MPa, and discharge temperature 50°C to 60°C.
[0022] In S5.2 of the above preparation method, the drying temperature is 70°C to 80°C.
[0023] Compared with the prior art, the method for preparing a carbon black-based composite conductive agent for automotive lithium batteries of the present invention has the following beneficial effects:
[0024] 1. MOF-Ni3(HITP)2 has a unique three-dimensional porous structure, which provides abundant channels and a large specific surface area for electron transmission, can enhance the interaction with carbon black, and make the transmission of electrons in the composite material more efficient. Compared with pure carbon black, MOF-Ni3(HITP)2 loaded with carbon black can form a more complete and continuous conductive network, thereby significantly improving the conductivity. Carbon black itself has a certain conductivity, but there is agglomeration phenomenon, which limits the performance of its conductive properties. Carbon black loaded on MOF-Ni3(HITP)2 reduces the agglomeration of carbon black due to the dispersion effect of MOF, so that the conductive properties of carbon black are better exerted. Carbon black reduces resistivity and achieves conductivity by forming a conductive network in the polymer matrix. The presence of MOF-Ni3(HITP)2 provides more attachment sites and conductive channels for carbon black. The synergistic effect of the two enables electrons to be transmitted more quickly in the composite material, thereby improving the overall conductive properties.
[0025] 2. During high current charge and discharge (i.e. rate performance test), MOF-Ni3(HITP)2 loaded with carbon black can better adapt to rapid electron transmission and ion diffusion. The porous structure of MOF is conducive to the penetration of electrolyte and the transmission of ions, while carbon black provides good electron conductivity. The combination of the two enables the composite material to maintain good performance stability of the battery under high rate charge and discharge. Pure carbon black is prone to local current concentration and electrode polarization during high rate charge and discharge due to the relatively poor stability of its conductive network, resulting in a decrease in rate performance. MOF-Ni3(HITP)2 loaded with carbon black has higher structural stability, which can effectively alleviate these problems and improve rate performance. Rate performance depends on the electron transmission speed and ion diffusion speed of the electrode material at high current density. The three-dimensional structure of MOF-Ni3(HITP)2 provides a channel for rapid transmission of ions and electrons, and the high conductivity of carbon black ensures the rapid transfer of electrons. The combined effect of the two enables the composite material to maintain good performance during high rate charge and discharge.
[0026] 3. MOF-Ni3(HITP)2 has high chemical stability and structural stability, and can maintain structural integrity during the charge and discharge process. The carbon black loaded on it can be protected by MOF, reducing the decrease in conductivity caused by volume changes and structural damage of the electrode material. Therefore, MOF-Ni3(HITP)2 loaded carbon black has better cycle stability and can maintain high conductivity after multiple charge and discharge cycles. Pure carbon black is easily corroded by the electrolyte and affected by the volume changes of the electrode material during long-term charge and discharge cycles, resulting in the destruction of the conductive network and relatively poor cycle performance. The quality of the cycle performance is closely related to the structural stability and conductivity stability of the electrode material during the charge and discharge process. The stable structure of MOF-Ni3(HITP)2 provides stable support and protection for carbon black, so that the composite material can maintain good conductivity and structural stability during long-term charge and discharge cycles, thereby improving the cycle performance.
[0027] Fourth, the present invention uses a spray to modify the surface of MOF-Ni3(HITP)2 loaded carbon black. In the spray, polyvinyl alcohol has good film-forming and adhesive properties, and can form a uniform thin film on the surface of MOF-Ni3(HITP)2 loaded carbon black, thereby improving the structural stability and mechanical strength of the composite material. At the same time, polyvinyl alcohol can also improve the adhesion between the electrode material and the current collector, reduce the shedding and damage of the electrode during the charging and discharging process, thereby improving the cycle performance and service life of the battery. Aqueous polyurethane has excellent flexibility and wear resistance, can improve the flexibility and wear resistance of the conductive agent material, reduce the damage of the electrode during use, and provide good protection for the composite material. Behenyl amide propyl dimethylamine has conductivity and dispersibility, which can improve the dispersibility of MOF-Ni3(HITP)2 loaded carbon black in the electrode slurry, reduce agglomeration, and improve the uniformity and consistency of the electrode. At the same time, behenyl amide propyl dimethylamine can also reduce the surface resistance of the electrode material and improve the conductivity of the battery. Fatty alcohol polyoxyethylene ether can improve the fluidity and coating performance of MOF-Ni3(HITP)2 loaded carbon black in the slurry, and can be more evenly coated on the current collector, thus improving the quality and performance of the electrode. Fatty alcohol polyoxyethylene ether is also beneficial to the penetration of electrolyte and the transmission of ions, thereby improving the rate performance and cycle performance of the battery. The use of fatty alcohol polyoxyethylene ether in combination with behenamidopropyl dimethylamine can improve the homogeneity of the coating agent.
[0028] 5. Dry MOF-Ni3(HITP)2 and irradiate it with ultraviolet light. Drying is used to remove moisture and volatile impurities and improve surface activity. Ultraviolet light irradiation changes the surface structure of the particles and improves their surface activity. It can also improve the deposition and bonding of conductive carbon black and improve conductivity.
[0029] 6. The present invention designs deposition parameters according to the deposition characteristics of conductive carbon black and the structural characteristics of MOF-Ni3(HITP)2. The heating rate is designed to be 5°C / min to 8°C / min to avoid thermal shock and uneven deposition of the sample. The deposition temperature is between 600°C and 800°C. If the temperature is too low, the carbon layer structure of carbon black will be unstable, and the carbon layer will be in a relatively messy stage, which will affect ion transport and the conductivity will be relatively poor. The gas flow rate is controlled at 500mL / min to 1500mL / min. Too much gas flow will affect the deposition stability of conductive carbon black, and too little flow will affect the deposition amount of conductive carbon black, which will in turn affect the decline in conductivity and the low battery charge and discharge efficiency. DETAILED DESCRIPTION
[0030] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.
[0031] Embodiment 1: A method for preparing a carbon black-based composite conductive agent for automotive lithium batteries, comprising the following steps:
[0032] S1, sample pretreatment: MOF-Ni3(HITP)2 powder was dried at 70 °C for 40 min and then irradiated with ultraviolet light for 40 min to improve the surface activity;
[0033] S2, sample loading: the pretreated MOF-Ni3(HITP)2 powder is evenly spread in an open container, placed in a chemical vapor deposition furnace, and evacuated to remove air and impurities;
[0034] S3, introducing gas: introducing gas into the chemical vapor deposition furnace, the gas flow rate is 1000 mL / min, the gas contains carrier gas and carbon source gaseous precursor, the volume ratio of carrier gas to carbon source gaseous precursor is 100:6; the carrier gas is nitrogen, and the carbon source gaseous precursor is acetylene;
[0035] S4, deposition of carbon black: the chemical vapor deposition furnace was heated to 700°C at a heating rate of 6°C / min, the gas flow rate was 1000mL / min, the deposition reaction was carried out for 2h, and the conductive carbon black was deposited on the surface and pores of MOF-Ni3(HITP)2, and the temperature was lowered and taken out to obtain MOF-Ni3(HITP)2 loaded carbon black;
[0036] S5, surface modification:
[0037] S5.1: Mix and prepare water: polyvinyl alcohol: water-based polyurethane: behenamidopropyl dimethylamine: fatty alcohol polyoxyethylene ether at a mass ratio of 90:1.8:1.0:1.0:0.5 at 50° C. to obtain a spray;
[0038] S5.2: Using a fluidized spray method, the MOF-Ni3(HITP)2 loaded carbon black is surface-coated and modified by spraying, and then dried at 75°C to obtain a carbon black-based composite conductive agent for automotive lithium batteries;
[0039] The parameters of fluidized spraying are: spray inlet temperature 32°C, spray speed 0.30L / min, atomization pressure 0.55MPa, and discharge temperature 55°C.
[0040] Embodiment 2: A method for preparing a carbon black-based composite conductive agent for automotive lithium batteries, comprising the following steps:
[0041] S1, sample pretreatment: MOF-Ni3(HITP)2 powder was dried at 60 °C for 20 min and then irradiated with ultraviolet light for 30 min to improve the surface activity;
[0042] S2, sample loading: the pretreated MOF-Ni3(HITP)2 powder is evenly spread in an open container, placed in a chemical vapor deposition furnace, and evacuated to remove air and impurities;
[0043] S3, introducing gas: introducing gas into the chemical vapor deposition furnace, the gas flow rate is 500 mL / min, the gas contains carrier gas and carbon source gaseous precursor, the volume ratio of carrier gas to carbon source gaseous precursor is 100:3; the carrier gas is nitrogen, and the carbon source gaseous precursor is acetylene;
[0044] S4, deposition of carbon black: the chemical vapor deposition furnace was heated to 600°C at a heating rate of 5°C / min, the gas flow rate was 800mL / min, the deposition reaction was carried out for 1.5h, and the conductive carbon black was deposited on the surface and pores of MOF-Ni3(HITP)2, and the temperature was lowered and taken out to obtain MOF-Ni3(HITP)2 loaded carbon black;
[0045] S5, surface modification:
[0046] S5.1: Mix and prepare water: polyvinyl alcohol: water-based polyurethane: behenamidopropyl dimethylamine: fatty alcohol polyoxyethylene ether in a mass ratio of 80:1:0.5:0.5:0.3 at 40° C. to obtain a spray;
[0047] S5.2: Using a fluidized spray method, the MOF-Ni3(HITP)2 loaded carbon black is surface-coated and modified by spraying, and then dried at 70°C to obtain a carbon black-based composite conductive agent for automotive lithium batteries;
[0048] The parameters of fluidized spraying are: spray inlet temperature 30°C, spray speed 0.25L / min, atomization pressure 0.5MPa, and discharge temperature 50°C.
[0049] Embodiment 3: A method for preparing a carbon black-based composite conductive agent for automotive lithium batteries, comprising the following steps:
[0050] S1, sample pretreatment: MOF-Ni3(HITP)2 powder was dried at 65 °C for 30 min and then irradiated with ultraviolet light for 35 min to improve the surface activity;
[0051] S2, sample loading: the pretreated MOF-Ni3(HITP)2 powder is evenly spread in an open container, placed in a chemical vapor deposition furnace, and evacuated to remove air and impurities;
[0052] S3, introducing gas: introducing gas into the chemical vapor deposition furnace, the gas flow rate is 600 mL / min, the gas contains carrier gas and carbon source gaseous precursor, the volume ratio of carrier gas to carbon source gaseous precursor is 100:4.5; the carrier gas is nitrogen, and the carbon source gaseous precursor is acetylene;
[0053] S4, deposition of carbon black: the chemical vapor deposition furnace was heated to 650°C at a heating rate of 6°C / min, the gas flow rate was 800 mL / min, the deposition reaction was carried out for 2 hours, and the conductive carbon black was deposited on the surface and pores of MOF-Ni3(HITP)2, and the temperature was lowered and taken out to obtain MOF-Ni3(HITP)2 loaded carbon black;
[0054] S5, surface modification:
[0055] S5.1: Mix and prepare water: polyvinyl alcohol: water-based polyurethane: behenamidopropyl dimethylamine: fatty alcohol polyoxyethylene ether in a mass ratio of 85:1.4:0.6:0.7:0.4 at 45°C to obtain a spray;
[0056] S5.2: Using a fluidized spray method, the MOF-Ni3(HITP)2 loaded carbon black is surface-coated and modified by spraying, and then dried at 72°C to obtain a carbon black-based composite conductive agent for automotive lithium batteries;
[0057] The parameters of fluidized spraying are: spray inlet temperature 32°C, spray speed 0.25L / min, atomization pressure 0.52MPa, and discharge temperature 52°C.
[0058] Embodiment 4: A method for preparing a carbon black-based composite conductive agent for automotive lithium batteries, comprising the following steps:
[0059] S1, sample pretreatment: MOF-Ni3(HITP)2 powder was dried at 75 °C for 50 min and then irradiated with ultraviolet light for 45 min to improve the surface activity;
[0060] S2, sample loading: the pretreated MOF-Ni3(HITP)2 powder is evenly spread in an open container, placed in a chemical vapor deposition furnace, and evacuated to remove air and impurities;
[0061] S3, introducing gas: introducing gas into the chemical vapor deposition furnace, the gas flow rate is 1200 mL / min, the gas contains carrier gas and carbon source gaseous precursor, the volume ratio of carrier gas to carbon source gaseous precursor is 100:8.5; the carrier gas is nitrogen, and the carbon source gaseous precursor is acetylene;
[0062] S4, deposition of carbon black: the chemical vapor deposition furnace was heated to 750°C at a heating rate of 7°C / min, the gas flow rate was 1200mL / min, the deposition reaction was carried out for 2.5h, and the conductive carbon black was deposited on the surface and pores of MOF-Ni3(HITP)2, and the temperature was lowered and taken out to obtain MOF-Ni3(HITP)2 loaded carbon black;
[0063] S5, surface modification:
[0064] S5.1: Mix and prepare at 55° C. the mass ratio of water: polyvinyl alcohol: water-based polyurethane: behenamidopropyl dimethylamine: fatty alcohol polyoxyethylene ether = 95:2.0:1.2:1.3:0.7 to obtain a spray;
[0065] S5.2: Using a fluidized spray method, the MOF-Ni3(HITP)2 loaded carbon black is surface-coated and modified by spraying, and then dried at 78°C to obtain a carbon black-based composite conductive agent for automotive lithium batteries;
[0066] The parameters of fluidized spraying are: spray inlet temperature 34°C, spray speed 0.32L / min, atomization pressure 0.58MPa, and discharge temperature 58°C.
[0067] Embodiment 5: A method for preparing a carbon black-based composite conductive agent for automotive lithium batteries, comprising the following steps:
[0068] S1, sample pretreatment: MOF-Ni3(HITP)2 powder was dried at 80 °C for 60 min and then irradiated with ultraviolet light for 50 min to improve the surface activity;
[0069] S2, sample loading: the pretreated MOF-Ni3(HITP)2 powder is evenly spread in an open container, placed in a chemical vapor deposition furnace, and evacuated to remove air and impurities;
[0070] S3, introducing gas: introducing gas into the chemical vapor deposition furnace, the gas flow rate is 1500 mL / min, the gas contains carrier gas and carbon source gaseous precursor, the volume ratio of carrier gas to carbon source gaseous precursor is 100:10; the carrier gas is nitrogen, and the carbon source gaseous precursor is acetylene;
[0071] S4, deposition of carbon black: the chemical vapor deposition furnace was heated to 800°C at a heating rate of 8°C / min, the gas flow rate was 1500mL / min, the deposition reaction was carried out for 3h, the conductive carbon black was deposited on the surface and pores of MOF-Ni3(HITP)2, the temperature was lowered and taken out, and MOF-Ni3(HITP)2 loaded carbon black was obtained;
[0072] S5, surface modification:
[0073] S5.1: Mix and prepare water: polyvinyl alcohol: water-based polyurethane: behenamidopropyl dimethylamine: fatty alcohol polyoxyethylene ether in a mass ratio of 100:2.5:1.5:1.5:0.8 at 60° C. to obtain a spray;
[0074] S5.2: Using a fluidized spray method, the MOF-Ni3(HITP)2 loaded carbon black is surface-coated and modified by spraying, and then dried at 80°C to obtain a carbon black-based composite conductive agent for automotive lithium batteries;
[0075] The parameters of fluidized spraying are: spray inlet temperature 35°C, spray speed 0.35L / min, atomization pressure 0.6MPa, and discharge temperature 60°C.
[0076] Embodiment 6: A method for preparing a carbon black-based composite conductive agent for automotive lithium batteries, comprising the following steps:
[0077] S1, sample pretreatment: MOF-Ni3(HITP)2 powder was dried at 80 °C for 30 min and then irradiated with ultraviolet light for 30 min to improve the surface activity;
[0078] S2, sample loading: the pretreated MOF-Ni3(HITP)2 powder is evenly spread in an open container, placed in a chemical vapor deposition furnace, and evacuated to remove air and impurities;
[0079] S3, introducing gas: introducing gas into the chemical vapor deposition furnace, the gas flow rate is 800 mL / min, the gas contains carrier gas and carbon source gaseous precursor, the volume ratio of carrier gas to carbon source gaseous precursor is 100:6.5; the carrier gas is argon gas, and the carbon source gaseous precursor is acetylene;
[0080] S4, deposition of carbon black: the chemical vapor deposition furnace was heated to 800°C at a heating rate of 5°C / min, the gas flow rate was 1200mL / min, the deposition reaction was carried out for 2h, and the conductive carbon black was deposited on the surface and pores of MOF-Ni3(HITP)2, and the temperature was lowered and taken out to obtain MOF-Ni3(HITP)2 loaded carbon black;
[0081] S5, surface modification:
[0082] S5.1: Mix and prepare water: polyvinyl alcohol: water-based polyurethane: behenamidopropyl dimethylamine: fatty alcohol polyoxyethylene ether in a mass ratio of 100:2.0:1.0:1.2:0.5 at 50° C. to obtain a spray;
[0083] S5.2: Using a fluidized spray method, the MOF-Ni3(HITP)2 loaded carbon black is surface-coated and modified by spraying, and then dried at 80°C to obtain a carbon black-based composite conductive agent for automotive lithium batteries;
[0084] The parameters of fluidized spraying are: spray inlet temperature 35°C, spray speed 0.35L / min, atomization pressure 0.6MPa, and discharge temperature 50°C.
[0085] The MOF-Ni3(HITP)2 powder used in the above embodiments has a particle length range of 400nm to 1μm, a diameter range of 19 to 26nm, a pore size of more than 2nm, and a specific surface area of less than 410m² / g, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0086] Comparative Example 1
[0087] In S1, the MOF-Ni3(HITP)2 powder is not dried and irradiated with ultraviolet light; other methods and parameters are the same as those in Example 1.
[0088] Comparative Example 2
[0089] In S4, the gas flow rate is 300 mL / min; other methods and parameters are the same as in Example 1.
[0090] Comparative Example 3
[0091] In S4, the gas flow rate is 2000 mL / min; other methods and parameters are the same as in Example 1.
[0092] Comparative Example 4
[0093] In S4, the temperature is raised to 500° C. to deposit carbon black; other methods and parameters are the same as in Example 1.
[0094] Comparative Example 5
[0095] S5 was omitted and no surface modification was performed; MOF-Ni3(HITP)2 loaded carbon black was directly used as the conductive agent; other methods and parameters were the same as those in Example 1.
[0096] Comparative Example 6
[0097] In S5.1, no behenamidopropyl dimethylamine is added to the spray, and the content of behenamidopropyl dimethylamine is replaced by water; other methods and parameters are the same as in Example 1.
[0098] Comparative Example 7
[0099] In S5.1, fatty alcohol polyoxyethylene ether is not added to the spray, and the content of fatty alcohol polyoxyethylene ether is replaced by water; other methods and parameters are the same as in Example 1.
[0100] Comparative Example 8
[0101] In S5.1, behenamidopropyl dimethylamine and fatty alcohol polyoxyethylene ether are not added to the spray, and the contents of behenamidopropyl dimethylamine and fatty alcohol polyoxyethylene ether are replaced by water; other methods and parameters are the same as in Example 1.
[0102] Comparative Example 9
[0103] Commercially available conventional conductive carbon black is used as the conductive agent. The particle size of conventional conductive carbon black is below 200 nm.
[0104] The conductive agents of the above-mentioned embodiments and comparative examples were tested in a trial manner.
[0105] Positive electrode slurry formula: lithium iron phosphate 92wt%, conductive agent 3wt%, polyvinylidene fluoride (PVDF) 5wt%; solvent is N-methylpyrrolidone (NMP), slurry system solid content 58%. Positive electrode sheet (coated on aluminum sheet) compaction density 2.0g / cm 3 .
[0106] Negative electrode slurry formula: artificial graphite 92.4wt%, commercial Super P 3wt%, SBR 3%, CMC 1.6wt%; solvent is deionized water, slurry system solid content 60%. Negative electrode sheet (coated on copper sheet) compaction density 1.6g / cm 3 .
[0107] Diaphragm: Polypropylene porous membrane.
[0108] Electrolyte: EC:DMC:EMC=1:1:1 (volume ratio), LiPF6 concentration is 1 mol / L.
[0109] The conductive agent of the positive electrode corresponds to the conductive agent of each embodiment and each comparative example.
[0110] Battery: 18650 battery samples were prepared according to the 18650 battery preparation method, and the amount of electrolyte added was 0.6g. Three parallel samples were made for each test. The performance test results are shown in Table 1 below.
[0111] Table 1 Electrical performance test results (average value)
[0112]
[0113] From the above results, it can be seen that the internal resistance of the batteries of Examples 1 to 5 is low, the charge and discharge are stable, and the first discharge efficiency and 500-week cycle efficiency are both high, indicating that the conductive agent can play a good conductivity and the conductivity is stable after long-term use. From the results of Comparative Example 1, it can be seen that the MOF-Ni3(HITP)2 powder is not dried and irradiated with ultraviolet rays, its surface activity is low, the deposition binding with conductive carbon black is poor, it is easily affected by pulping and use, and the conductivity and stability are relatively reduced. From the results of Comparative Examples 2 and 3, it can be seen that too large a flow rate of the deposition gas will affect the deposition stability of the conductive carbon black, and too small a flow rate will affect the deposition amount of the conductive carbon black, and then will affect the decrease in conductivity, which will affect the low charge and discharge efficiency of the battery. From the results of Comparative Example 4, it can be seen that at 500°C deposition, the temperature is low, the carbon layer structure of carbon black is unstable, and the carbon layer is in a relatively messy stage, which affects ion transport and has relatively poor conductivity. From the results of Comparative Example 5, it can be seen that the MOF-Ni3(HITP)2 loaded carbon black is not surface modified, which affects the dispersibility of the conductive agent, the conductive performance is unstable, and the loaded carbon black layer is easily affected by the mixing and battery charging and discharging, resulting in structural changes, carbon black layer shedding and other problems, which seriously affect the stability of the charge and discharge efficiency, and the charge and discharge efficiency drops significantly after long-term use. From the results of Comparative Examples 6 to 8, it can be seen that behenamide propyl dimethylamine and fatty alcohol polyoxyethylene ether can provide stability for the surface coating, the surface coating is more uniform, the coating modification quality is improved, the conductive agent structure is not easy to dissociate, the use stability of the conductive agent is improved, and long-term use can ensure a higher charge and discharge efficiency. From the results of Comparative Example 9, it can be seen that the conductivity and conductive stability of the conductive agent used alone as the positive electrode conductive agent are far inferior to those of the conductive agent in the embodiment, indicating that the conductive agent in the embodiment has a good conductive effect.
Claims
1. A method for preparing a carbon black-based composite conductive agent for automotive lithium batteries, characterized in that: The preparation method comprises the following steps: S1, sample pretreatment: drying the MOF-Ni3(HITP)2 powder and then irradiating it with ultraviolet light to increase the surface activity; S2, sample loading: the pretreated MOF-Ni3(HITP)2 powder is evenly spread in an open container, placed in a chemical vapor deposition furnace, and evacuated to remove air and impurities; S3, introducing gas: introducing gas into the chemical vapor deposition furnace, wherein the gas contains a carrier gas and a carbon source gaseous precursor, and the volume ratio of the carrier gas to the carbon source gaseous precursor is 100:(3-10); S4, depositing carbon black: heating the chemical vapor deposition furnace to 600°C to 800°C, with a gas flow rate of 800mL / min to 1500mL / min, and performing a deposition reaction for 1.5h to 3h to deposit the conductive carbon black on the surface and in the pores of MOF-Ni3(HITP)2, cooling and taking out, and obtaining MOF-Ni3(HITP)2 loaded carbon black; S5, surface modification: S5.1: Mix and prepare the following according to the mass ratio: water: polyvinyl alcohol: water-based polyurethane: behenamidopropyl dimethylamine: fatty alcohol polyoxyethylene ether = (80-100): (1-2.5): (0.5-1.5): (0.5-1.5): (0.3-0.8) to obtain a spray; S5.2: The surface of MOF-Ni3(HITP)2 loaded with carbon black is modified by a fluidized spraying method, and then dried to obtain a carbon black-based composite conductive agent for automotive lithium batteries.
2. The method for preparing a carbon black-based composite conductive agent for automotive lithium batteries according to claim 1, characterized in that: In S1, the drying is vacuum drying, the drying temperature is 60° C. to 80° C., and the drying time is more than 20 minutes.
3. The method for preparing a carbon black-based composite conductive agent for automotive lithium batteries according to claim 1, characterized in that: In S1, the ultraviolet irradiation time is 30 minutes to 50 minutes.
4. The method for preparing a carbon black-based composite conductive agent for automotive lithium batteries according to claim 1, characterized in that: In S3, the carrier gas is nitrogen or argon, and the carbon source gaseous precursor is acetylene.
5. The method for preparing a carbon black-based composite conductive agent for automotive lithium batteries according to claim 1, characterized in that: In S3, the flow rate of the gas is 500 mL / min to 1500 mL / min.
6. The method for preparing a carbon black-based composite conductive agent for automotive lithium batteries according to claim 1, characterized in that: In S4, the heating rate is 5°C / min to 8°C / min.
7. The method for preparing a carbon black-based composite conductive agent for automotive lithium batteries according to claim 1, characterized in that: In S5.1, the mixing temperature is 40°C to 60°C.
8. The method for preparing a carbon black-based composite conductive agent for automotive lithium batteries according to claim 1, characterized in that: In S5.2, the parameters of the fluidized spray are: spray inlet temperature 30°C to 35°C, spray speed 0.25L / min to 0.35L / min, atomization pressure 0.5MPa to 0.6MPa, and discharge temperature 50°C to 60°C.
9. The method for preparing a carbon black-based composite conductive agent for automotive lithium batteries according to claim 1, characterized in that: In S5.2, the drying temperature is 70°C to 80°C.
Citation Information
Patent Citations
Sulfur-loaded MOF@ conductive polymer material and preparation method and application thereof
CN108565464A
Novel lithium-sulfur battery cathode material and preparation method thereof
CN109301191A